Impact of LAB Consortia Supplementation and Teat Dipping on Haematological Parameters, Antioxidant Activity, and Total Immunoglobulin in subclinical mastitis Sahiwal Cows - Kumar, Sachin; Chauhan, Nutan; Balaga, Sravani; Singh, Ojal; Kundgir, Sumit; Samanta, Ashis Kumar (Indian Journal of Dairy Science, 2026)
The present study investigates the effects of a probiotic consortium on haematological parameters, antioxidant levels, and serum immunoglobulin concentrations in Sahiwal cows diagnosed with subclinical mastitis. A total of 24 mid-lactating cows were randomized into four treatment groups: a healthy control group (H) receiving fermented soybean meal (UFSB45), a subclinical mastitis group (M) also receiving UFSB45, a probiotic group (PRO) receiving an inoculated fermented soybean meal (IFSB45), and a combined treatment group (PRO+T) receiving IFSB45 along with topical teat dip application. The teat dip was administered at a concentration of 8.94 to 8.77 log10 CFU/ml, while the oral probiotic was given at a rate of 50 g per animal per day for 60 days. Results indicated no significant differences in dry matter intake (DMI) and body weight across treatment groups. However, hemoglobin (Hb) levels showed significant variation, with the healthy group exhibiting the highest Hb concentrations. Total leukocyte count (TLC) was significantly (p